The real Benedict Arnold - Murphy, Jim, 1947- (Clarion Books, 2007)
"Drawing on Arnold's surviving writings and on the letters, memoirs, and political documents of his contemporaries ... a fascinating portrait of a brilliant man, consistently undervalued by his peers, who made a choice that continues to reverberate through American history."